Intra-tumoral Heterogeneity of KRAS and BRAF Mutation Status in Patients with Advanced Colorectal Cancer (aCRC) and Cost-Effectiveness of Multiple Sample Testing - Susan D. Richman; Philip Chambers; Matthew T. Seymour; Catherine Daly; Sophie Grant; Gemma Hemmings; Philip Quirke (Analytical Cellular Pathology)
KRAS mutation status is established as a predictive biomarker of benefit from anti-EGFr therapies. Mutations are normally assessed using DNA extracted from one formalin-fixed, paraffin-embedded (FFPE) tumor block. We assessed heterogeneity of KRAS and BRAF mutation status intra-tumorally (multiple blocks from the same primary tumor). We also investigated the utility and efficiency of genotyping a ‘DNA cocktail’ prepared from multiple blocks. We studied 68 consenting patients in two randomized clinical trials. DNA was extracted, from ≥2 primary tumor FFPE blocks per patient. DNA was genotyped by pyrosequencing for KRAS codons 12, 13 and 61 and BRAF codon 600. In patients with heterogeneous mutation status, DNA cocktails were prepared and genotyped. Among 69 primary tumors in 68 patients, 7 (10.1%) showed intratumoral heterogeneity; 5 (7.2%) at KRAS codons 12, 13 and 2 (2.9%) at BRAF codon 600. In patients displaying heterogeneity, the relevant KRAS or BRAF mutation was also identified in ‘DNA cocktail’ samples when including DNA from mutant and wild-type blocks. Heterogeneity is uncommon but not insignificant. Testing DNA from a single block will wrongly assign wild-type status to 10% patients. Testing more than one block, or preferably preparation of a ‘DNA cocktail’ from two or more tumor blocks, improves mutation detection at minimal extra cost.